Fenomena Hubungan Parasosial Penggemar dan Idol K-Pop dalam Penggunaan Aplikasi Weverse - Dwi Hasnidar Sysca; Kadek Dristiana Dwivayani (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The K-Wave phenomenon that swept the world is certainly still being felt today. Assisted by the development of social media that is getting bigger and bigger in demand because of its features that make distance more meaningless. So this research will examine the parasocial relationship between fans and K-Pop idol TREASURE on the Weverse application which is popular among K-Pop fans. The application is supported by various features that allow fans to exchange information and messages with idols and even other TREASURE fans. TREASURE often replies to its fans through Weverse randomly or for lucky fans. Fans finally feel an interaction when using the application even though only fan representatives are replied to by TREASURE members. Other fans also feel the interpersonal communication between themselves and their idols. This can be called a parasocial relationship, which is a one-way relationship felt by fans. Where this research aims to see, describe, and analyse how the phenomenon of parasocial relationships between TREASURE MAKERS in Samarinda and TREASURE in using the Weverse application. Using the classification of levels of parasocial relationships and Social Information Processing theory as supporting arguments when the research results are found. Then this research has a qualitative descriptive type by showing the research results that the phenomenon of parasocial relationships between TREASURE MAKER and TREASURE fans has passed all three levels, namely Entertainment Social Value, Intense Personal Feeling, and Borderline Pathological so that in theory the SIP informants in this study show an extraordinary feeling of closeness to their idols through the help of the Weverse application.